한식정보 활용을 위한 온톨로지 설계에 관한 연구 - 유하경(Ha-Gyeong Yu); 박옥남(Ok Nam Park) (한국콘텐츠학회 논문지, 19(2), 2019)
The Korean food, which has been attracting attention only as a unique culture of Korea, has become popular in the world market by being used as a material of Korean Wave and me-media. The systematic organization of knowledge for recipes and related information can highlight the value of Korean food. It will serve as a basis for improving the reusability of Korean food contents through expanded and limited search and effective browsing. This study purports to design an ontology for establishing Korean food knowledge structure. Ontology modeling is based on OWL. Vocabularies of Korean food were examined based on 32 volumes of Korean food information, and data elements were extracted by analyzing five domains and applications. As a result, the study derived classes and properties, and proposed an indexing example. 한국의 고유문화로만 주목을 받아온 한식은 한류 및 1인 미디어의 소재로 활용되며 세계 시장 속에서 인기를 이어가고 있다. 한식의 조리법에 더하여 한식의 가치를 부각시켜줄 수 있는 관련 자료들을 체계적으로 조직하는 것은 확장 및 제한검색, 효과적인 브라우징을 통한 한식 콘텐츠의 재사용성을 향상시키는 데 토대가 된다. 이에 본 연구는 한식 지식구조의 정립을 위한 온톨로지의 설계를 목적으로 한다. 온톨로지 모델링은 OWL을 활용하였으며, 한식 정보를 담고 있는 32권의 단행본을 기반으로 한식의 유형 및 어휘를 조사하고, 음식 정보를 기반으로 하는 5개의 도메인 및 어플리케이션을 분석하여 데이터요소를 추출하였다. 연구결과 클래스 및 관련 속성을 도출하였고, 클래스별 속성과 색인예를 제시하였다.